Carbapenem-resistant Enterobacterales colonization and subsequent infection in a neonatal intensive care unit in Shanghai, China. Issue 3 (September 2021) - Yin, L.; He, L.; Miao, J.; Yang, W.; Wang, X.; Ma, J.; Wu, N.; Cao, Y.; Wang, C.
SUMMARY: Background: Colonization has been reported to play an important role in carbapenem-resistant Enterobacterales (CRE) infection; however, the extent to which carriers develop clinical CRE infection and related risk factors in neonatal intensive care unit (NICU) patients is unclear. Aim: To investigate the frequency of CRE colonization and its contribution to infections in NICU patients. Methods: CRE colonization screening and CRE infection surveillance were performed in the NICU in 2017 and 2018. Findings: Among 1230 unique NICU patients who were screened for CRE colonization, 144 patients tested positive (11.7%, 144/1230), with 9.2% (110/1197) in the intestinal tract, which was higher than that in the upper respiratory tract (6.6%, 62/945) ( P =0.026). Gestational age, low birth weight and prolonged hospitalization were risk factors for CRE colonization (all P <0.001). Diversilab homology monitoring found an overall 17.4% (25/144) risk of infection among patients colonized with CRE. For carbapenem-resistant Klebsiella pneumoniae (CR-KP) and carbapenem-resistant Escherichia coli (CR-ECO), the risks were 19.1% (21/110) and 13.8% (4/29), respectively. The independent risk factors for CR-KP clinical infection among CR-KP carriers were receiving mechanical ventilation (odds ratio (OR), 10.177; 95% confidence interval (CI), 2.667–38.830; P =0.013), a high level of neonatal nutritional risk assessment (OR, 0.251; 95% CI, 0.072–0.881; P =0.031) and a high neonatal acute physiology II (SNAP-II) score (OR, 0.256; 95% CI, 0.882–1.034; P =0.025). Conclusions: The colonization of CRE may increase the incidence of corresponding CRE infection in NICU patients. Receiving mechanical ventilation, malnutrition and critical conditions with high SNAP-II scores were independent risk factors for subsequent CR-KP clinical infection.